Analyze code through C++ and Code::Blocks programming languages (Ciencias de la Ingeniería y Aplicadas, 2019)
This article deals with the analysis to be carried out of a code using nested data structures, which are grouped into integer, char, and floating data, characterizing their organization and the relationships between the data that constitute it. To develop a program applying constant values ​​that refer to already permanent data and integer type variables as well as counters to obtain accumulated values ​​and total sum of trips, such as drawers for n companies, which distribute the products already specified in the program with to obtain the greatest sale and ordering, such as its search through an auto-generated code, we have taken an execution time in the program for which the C++ and Code: Blocks programming language will be used, since it is a flexible language that works with the structured programming with the possibility of defining source code files, and for the proper execution of the program it is done in Dev c++ and Code: Blocks. In addition to the use of structures, functions with parameters are also used and in turn by value, by reference that return values ​​within the code. Modular programming is made up of specific tasks that are declared independently, and these in turn seek to be solved in parts, this is about dividing the program into sub-programs that allow the reduction of the code for a better understanding and in this way it can be applied in any development IDE such as Code: Blocks.Code
Keywords: Code; Development; Nested Structures; Features; Program